Azygos vein preservation is feasible and beneficial in esophageal atresia with tracheoesophageal fistula: A meta-analysis of randomized controlled trials - Wang, Chuan; Zheng, Junkai; Ma, Xue (Frontiers in Pediatrics, 2022)
Background: Esophageal atresia (EA) with tracheoesophageal fistula (TEF) is a common congenital anomaly. It is still unknown whether azygos vein preservation will increase the difficulty or time of operation and reduce the quality of anastomosis. Thus, we conducted this meta-analysis to explore the puzzle. Methods: Two researchers independently searched the databases. Randomized controlled trials were included if these studies applied thoracotomy to perform operations and compared the outcomes in patients with EA/TEF between azygos vein preservation groups and azygos vein ligation groups. The Jadad score was used to assess the quality of the included studies. Statistical heterogeneity was evaluated using the I2 value. A fixed or random-effect model was applied regarding the I2 value. Results: Four studies involving 286 patients were included. The pooled estimates indicated that preservation of the azygos vein decreased the incidence of anatomic leakage with a pooled risk ratio (RR) of 0.54 (95% CI 0.29-0.99, P=0.05) and mortality with an RR of 0.51 (95% CI 0.29-0.90; P=0.02). Preservation of the azygos vein might not require a longer operative time than ligation of the azygos vein. Conclusions: This research certifies that preservation of the azygos vein is able to reduce the prevalence of anastomotic leakage and mortality.